The Extent of Implementation of The Local Government Unit of RA 9262 in Eliminating Violence Against Women and Children in the National Capital Region - Matahum, Atty Ferolini T.; Tanigue, Yolanda G. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
This study examined the gender sensitivity of the Philippine government’s response during a public health crisis, with a particular emphasis on the viewpoints of local government units (LGUs) and their stakeholders. The study aimed to analyze the challenges and opportunities encountered by LGUs in maintaining gender-responsive services during these periods. The study sought to align the national policy framework with the realities of its implementation, emphasizing effective and scalable practices that could guide future rights-based and gender-sensitive approaches, particularly in decentralized governance systems frequently neglected during biological emergencies. The study employed a descriptive comparative research design, collecting data via surveys directed at four primary government offices: the Rural Health Unit (RHU), City Social Welfare and Development (CSWD), Philippine National Police (PNP), and Barangay officials. Participants were selected using stratified random sampling, resulting in a total of 135 individuals. The primary instrument employed was a questionnaire modified from Alincastre and Dalugdog (2022), with results analyzed through weighted mean and one-way ANOVA. The results indicated that most respondents were college-educated women aged 31 to 40, the majority of whom had participated in training or seminars concerning the Violence Against Women and Children (VAWC) Act, or Republic Act 9262. A significant number exhibited a comprehensive understanding of the law, encompassing case filing procedures, the associated legal mechanisms, and the penalties applicable to offenders. The study identified deficiencies at the Barangay level, specifically in proper documentation, case management, and the issuance of Barangay Protection Orders. These issues indicate the necessity for a more organized and adequately supported system. The researcher proposed a policy enhancement through a joint memorandum circular issued by the Department of the Interior and Local Government (DILG), the Department of Health (DOH), and the Department of Social Welfare and Development (DSWD) to address these challenges. This would enable Barangays to execute their responsibilities under RA 9262 with greater efficacy. The research highlighted the essential importance of collaboration among agencies. A multi-disciplinary team comprising investigators (PNP), social workers (DSWD), health officers, medico-legal professionals, and local councils (e.g., Barangay Council for the Protection of Children) should collaborate to deliver comprehensive services. These encompass health care, psychological and educational support, legal assistance, and safety services for women and children. Furthermore, training programs and seminars must persist in promoting awareness and tackling gender-based discrimination and human rights violations. Economic empowerment is recognized as a vital strategy. Collaborating with the Local Government Unit (LGU) and the Department of Social Welfare and Development (DSWD), barangays ought to endorse livelihood programs that enhance women's involvement in local economic activities, thereby mitigating their vulnerability. Simultaneously, prioritizing the promotion of a culture of women's safety in public spaces is essential. The study emphasized the necessity of establishing mechanisms for victims of rights violations, including access to protection orders, assistance in filing cases, and the collection of essential documents for prosecuting offenders. Annual training programs on the VAWC law should be conducted for LGUs in partnership with the Women and Children Protection Desk of the PNP, with enhanced seminars emphasizing the proper issuance and management of Barangay Protection Orders. The study concluded with a recommendation for additional research. Future research should incorporate a wider array of external stakeholders and utilize a qualitative methodology to enhance comprehension of the intricate realities present in the field.